Prescribing patterns of evidence-based heart failure pharmacotherapy and outcomes in the ASIAN-HF registry: a cohort study - Tiew‐Hwa Katherine Teng; Jasper Tromp; Wan Ting Tay; Inder S. Anand; Wouter Ouwerkerk; Vijay Chopra; Gurpreet Singh Wander; Jonathan JL Yap; Michael R. MacDonald; Chang Xu; Yvonne M.F. Chia; Wataru Shimizu; et al. (2018)
Angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), β blockers, and mineralocorticoid receptor antagonists (MRAs) are of proven benefit and are recommended by guidelines for management of patients with heart failure and reduced ejection fraction (HFrEF). We aimed to examine the first prospective multinational data from Asia on prescribing patterns of guideline-directed medical therapies and analyse its effect on outcomes.In the prospective multinational ASIAN-HF registry (with enrolment from 46 centres in 11 countries in Asia), we enrolled patients aged 18 years or older, with symptomatic heart failure (stage C, with at least one episode of decompensated heart failure in the past 6 months that resulted in admission to hospital or was treated in an outpatient clinic) and left ventricular systolic dysfunction (ejection fraction ≤40% on baseline echocardiography, consistent with 2016 European Society of Cardiology guidelines). We excluded patients with heart failure caused by severe valvular heart disease, life-threatening comorbidity with a life expectancy of less than 1 year, who were unable or unwilling to give consent, or who had concurrent participation in a clinical trial. Patients were followed up for 3 years for the outcomes of death and cause-specific admittance to hospital. Primary outcomes were uptake of guideline-directed medical therapies (as proportions) by therapeutic class, achieved doses as proportions of guideline-recommended doses, and their association with 1-year composite outcome of all-cause death or admittance to hospital because of heart failure. This study is registered with ClinicalTrials.gov, number NCT01633398.Between Oct 1, 2012, and Dec 31, 2015, we enrolled 5276 patients with HFrEF (mean age 59·6 years [SD 13·2], 77% men, body-mass index 24·9 kg/m2 [5·1], 33% New York Heart Association class III or IV). Follow-up data were available for 4544 (90%) of 5061 eligible patients taking medication for heart failure, with median follow-up of 417 days (IQR 214-735). ACE inhibitors or ARBs were prescribed to 3868 (77%) of 5005 patients, β blockers to 3975 (79%) of 5061, and MRAs to 2998 (58%) of 5205, with substantial regional variation. Guideline-recommended dose was achieved in only 17% of cases for ACE inhibitors or ARB, 13% for β blockers, and 29% for MRAs. Country (all three drug classes), increasing body-mass index (ACE inhibitors or ARBs and MRAs), and in-patient recruitment (ACE inhibitors or ARBs and β blockers) were associated with attainment of guideline-recommended dose (all p<0·05). When adjusted for indication bias, increasing drug doses, from low dose (1-<25% of guideline-recommended dose) upwards were associated with lower hazards of a 1-year composite outcome for ACE inhibitors or ARBs and β blockers compared with non-users. The lowest adjusted hazards were in the group that attained guideline-recommended doses above 50% (hazard ratio [HR] 0·54, 95% CI 0·50-0·58 for ACE inhibitors or ARBs [50-99·9%]; HR 0·47, 0·46-0·50 for β blockers, and HR 0·77, 0·72-0·81 for MRAs [≥100%]).Guideline-directed medical therapies at recommended doses are underutilised in patients with HFrEF. Improved uptake and uptitration of guideline-directed medical therapies are needed for better patient outcomes.National Medical Research Council (Singapore), A*STAR Biomedical Research Council ATTRaCT program, Boston Scientific Investigator Sponsored Research program, and Bayer.